1996
DOI: 10.1006/dbio.1996.0043
|View full text |Cite
|
Sign up to set email alerts
|

A Member of the Phylogenetically Conserved CAD Family of Transcriptional Regulators Is Dramatically Up-Regulated during the Programmed Cell Death of Skeletal Muscle in the Tobacco HawkmothManduca sexta

Abstract: The intersegmental muscles (ISMs) of the tobacco hawkmoth Manduca sexta participate in the emergence behavior of the adult moth at the end of metamorphosis and then die during the subsequent 30-hr period. The trigger for this death is a decline in the circulating titer of the insect molting hormone 20-hydroxyecdysone (20-HE). Previous work has demonstrated that the ability of the ISMs to die is dependent on new gene expression. Using a differential hybridization cloning strategy, a cDNA library made from the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…The requirement for de novo protein synthesis in involution of the ISMs (Lockshin, 1969,Wadewitz andLockshin, 1988) has been clearly linked to transcriptional regulation through molecular cloning of both up-and down-regulated genes (Schwartz et al, 1990). Genes for actin, myosin and the 20S proteasome unit are downregulated (Schwartz et al, 1993;Jones et al, 1995), while those for polyubiquitin , the 26S proteasome units and other proteins are up-regulated at the onset of involution (Dawson et al, 1996, Kuelzer et al, 1999Sun et al, 1996;Low et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for de novo protein synthesis in involution of the ISMs (Lockshin, 1969,Wadewitz andLockshin, 1988) has been clearly linked to transcriptional regulation through molecular cloning of both up-and down-regulated genes (Schwartz et al, 1990). Genes for actin, myosin and the 20S proteasome unit are downregulated (Schwartz et al, 1993;Jones et al, 1995), while those for polyubiquitin , the 26S proteasome units and other proteins are up-regulated at the onset of involution (Dawson et al, 1996, Kuelzer et al, 1999Sun et al, 1996;Low et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…56 In fact, ISM death is associated with a coordinated increase in all components of the ubiquitin-proteasome pathway, including: ubiquitin, 20S and 26S proteasome subunits, and E2 ubiquitin protein conjugases. 41,59,66,57 The induction of the ubiquitin-proteasome pathway presumably serves to facilitate protein loss during PCD, especially since the cells are not phagocytosed. 46 Bayline et al 32 have shown that pharmacological inhibition of the proteasome is sufficient to block the initiation of ISM death.…”
Section: Molecular Mechanisms Controlling Atrophy and Deathmentioning
confidence: 99%
“…The death of the ISMs depends on de novo gene expression, and several death-associated transcripts have been identified (12). A number of these proteins have been shown to be phylogenetically conserved and capable of functioning in cells from a wide variety of taxa (13). In this report, we describe the cloning and analysis of DALP (deathassociated LIM-only protein) and demonstrate that it and its mammalian ortholog Hic-5 (14) act as negative regulators of muscle differentiation in insects and mammals.…”
mentioning
confidence: 99%